Clinical effects and safety of electroacupuncture for the treatment of allergic rhinitis: A protocol for systematic review - Fu, Li (Medicine (Baltimore), 2020)
BACKGROUND: As the therapy of acupuncture continues to expand, electroacupuncture is increasing used in allergic rhinitis prevention and therapy, and many studies have published that it is effective in the treatment of allergic rhinitis. However, it is unclear if electroacupuncture provides an evidence-based clinical benefit in the allergic rhinitis population. METHODS/DESIGN: We will conduct a systematic review of electroacupuncture and health-related outcomes in allergic rhinitis patients according to the Preferred Reporting Items for Systematic Reviews. The primary objective is to assess the impact of Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines on clinical outcomes relevant to allergic rhinitis patients, such as effective rate, life-quality evaluation, and adverse events. The Cochrane Risk Assessment Tool will be used to assess the quality of eligible studies according to the Cochrane handbook. RESULTS: We will perform a meta-analysis using standard techniques for the outcomes. CONCLUSION: The results of this systematic review may highlight the gaps in our knowledge of the relevance of electroacupuncture after treatment or after follow-ups. PROSPERO registration number: PROSPERO CRD42018104080. (https://www.crd.york.ac.uk/PROSPERO/#recordDetails)